Norovirus Disease Among Children <5 Years in 3 Sub-Saharan African Countries: Findings From the Vaccine Impact on Diarrhea in Africa (VIDA) Study, 2015–2018. (19th April 2023) - Omore, Richard; Powell, Helen; Sow, Samba O; Jahangir Hossain, M; Ogwel, Billy; Doh, Sanogo; Ochieng, John B; Jones, Joquina Chiquita M; Zaman, Syed M A; Awuor, Alex O; Juma, Jane; Kasumba, Irene N; et al.
Abstract: Background: To address a paucity of data from sub-Saharan Africa, we examined the prevalence, severity, and seasonality of norovirus genogroup II (NVII) among children <5 years old in The Gambia, Kenya, and Mali following rotavirus vaccine introduction. Methods: Population-based surveillance was conducted to capture medically-attended moderate-to-severe diarrhea (MSD) cases, defined as a child 0–59 months old passing ≥3 loose stools in a 24-hour period with ≥1 of the following: sunken eyes, poor skin turgor, dysentery, intravenous rehydration, or hospitalization within 7 days of diarrhea onset. Diarrhea-free matched controls randomly selected from a censused population were enrolled at home. Stools from cases and controls were tested for enteropathogens, including norovirus and rotavirus, by TaqMan quantitative polymerase chain reaction (PCR) and conventional reverse transcription PCR. We used multiple logistic regression to derive adjusted attributable fractions (AFe) for each pathogen causing MSD, which takes into consideration the prevalence in both cases and controls, for each site and age. A pathogen was considered etiologic if AFe was ≥0.5. In further analyses focusing on the predominant NVII strains, we compared rotavirus and NVII severity using a 20-point modified Vesikari score and examined seasonal fluctuations. Results: From May 2015 to July 2018, we enrolled 4840 MSD cases and 6213 controls. NVI was attributed to only 1 MSD episode. NVII was attributed to 185 (3.8%) of all MSD episodes and was the sole attributable pathogen in 139 (2.9%); peaking (36.0%) at age 6–8 months with majority (61.2%) aged 6–11 months. MSD cases whose episodes were attributed to NVII alone compared with rotavirus alone were younger (median age, 8 vs 12 months, P < .0001) and had less severe illness (median Vesikari severity score, 9 vs 11, P = .0003) but equally likely to be dehydrated. NVII occurred year-round at all study sites. Conclusions: Infants aged 6–11 months bear the greatest burden of norovirus disease, with NVII predominating. An early infant vaccine schedule and rigorous adherence to guidelines recommended for management of dehydrating diarrhea may offer substantial benefit in these African settings. Abstract : Norovirus genogroup II was the attributed etiology for 3% of all moderate-to-severe diarrhea (MSD) cases among children <5 years old in The Gambia, Mali, and Kenya post-rotavirus vaccine introduction; the highest disease burden concentrated in children 6–11 months old.